Sequence based prediction of putative transcription factors binding sites in the 5’-upstream region of Toll-like receptor 8 gene in Indian goats - Goyal, Shubham; Dubey, P.K.; P. Kathiravan; Mishra, B.P.; Mahajan, Ritu; Kataria, RS. (Journal of Livestock Biodiversity, 2025)
Toll-like receptor 8 (TLR8) recognizes single stranded RNA (ssRNA) and is localized in endosomes. Stimulation of TLR8 by ligands activates the production of pro-inflammatory cytokines such as different tumour necrosis factors, interleukins etc. In this study approximately 1.1Kb of 5’-upstream region of goat TLR8 gene was amplified and characterized for the presence of different putative transcription binding factor sites. The sequence analysis revealed the goat TLR8 to be closer to cattle sharing 88% homology followed by other species in the 5-upstream region. The sequence analysis for the search of putative binding sites for transcription factors, showed the presence of 70 potential sites in goat as compared to cattle, where it was found to be having 76 sites in the same region scanned. Further analysis showed the insertion of five nucleotides in goat at two different positions as compared to cattle. The binding factor sites analysis revealed the presence of some important factors binding sites such as PU-1, an important regulatory elements in goat, found to be absent in cattle. Many of the factors were found to be similar in both the species sharing the same position in the sequence. Overall our results showed the presence of important regulatory elements in goat TLR8 5’upstream, which may be important for understanding the regulation of its transcription.